BACTERIAL CELLULOSE INCORPORATED ZINC PHOSPHATE NANOCOMPOSITE FOR ANTIBACTERIAL AGENT AND AIR PARTICULATE MATTER FILTRATION - Nurhidayah Nurhidayah; Ramadhan, La Ode Ahmad Nur -; Abdul Haris Watoni; Laode Abdul Kadir; Muhammad Daffa Rahmatullah; Cindy Agriningsih Haruna (Malaysian Journal of Science, 2024)
This study investigates the synthesis and the antibacterial properties of bacterial cellulose (BC) incorporated zinc phosphate nanocomposite-mediated dragon fruit extract (BC-ZP-DF). The composite was prepared by a three-step process that involved bacterial cellulose (BC), zinc phosphate (ZP), and nanocomposite BC-ZP synthesis. BC was prepared by fermenting coconut water with the components of ammonium sulfate, acetic acid, and Acetobacter xylinum culture. Zinc phosphate was made through the green synthesis method by reacting zinc nitrate and diammonium hydrogen phosphate using a sensitizer agent from red dragon fruit peel extract (DF) with volume variations of 5, 10, 20, 30, 40, and 50 mL. The composite was prepared by immersing BC with zinc phosphate. Phase crystallinity, functional group, and morphology of the samples were characterized using XRD, FTIR, and SEM. It was found that the nanocomposite was constructed by the nano green of zinc phosphate in the form of a hopeite structure with antibacterial PO43- and OH functional groups. Morphological analysis using SEM revealed that the nanocomposites contained various small powder grains. Based on the FTIR spectrum, XRD pattern, and surface morphology of composite film, the incorporation of zinc phosphate in the BC framework was confirmed. The antibacterial activity tests of nanocomposite films using Staphylococcus aureus and Pseudomonas aeruginosa bacteria revealed that the nanocomposite was highly effective in inhibiting both bacteria, and the nanocomposite BC-ZP-DF10 film had the strongest inhibition. The results of the air filter test exhibited that the composition was efficient on all films with the highest percent of efficiency (%E) of 90.10%.